2015
DOI: 10.1111/jocn.13104
|View full text |Cite
|
Sign up to set email alerts
|

Use of a single parameter track and trigger chart and the perceived barriers and facilitators to escalation of a deteriorating ward patient: a mixed methods study

Abstract: Citation: Smith, D. J. & Aitken, L. M. (2016). Use of a single parameter track and trigger chart and the perceived barriers and facilitators to escalation of a deteriorating ward patient: a mixed methods study. Journal of Clinical Nursing, 25(1-2), pp. 175-185. doi: 10.1111/jocn.13104 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent TITLE:Use of a single parameter track and trigger chart and the perceived barriers and facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Foley and Dowling () also identify some challenges around parameter adjustment; in that study, nurses said they believed they could use their own knowledge to adjust the parameters. Prior studies have suggested that nurses need clear structure and support for deciding when to assess the vital signs of patients at risk of deterioration (Johnson, Mueller, & Winkelman, ; Smith & Aitken, ). An absence of guidelines for when to assess vital signs leads to inconsistency in both assessment and documentation (Stevenson, Israelsson, Petersson, & Bath, ).…”
Section: Discussionmentioning
confidence: 99%
“…Foley and Dowling () also identify some challenges around parameter adjustment; in that study, nurses said they believed they could use their own knowledge to adjust the parameters. Prior studies have suggested that nurses need clear structure and support for deciding when to assess the vital signs of patients at risk of deterioration (Johnson, Mueller, & Winkelman, ; Smith & Aitken, ). An absence of guidelines for when to assess vital signs leads to inconsistency in both assessment and documentation (Stevenson, Israelsson, Petersson, & Bath, ).…”
Section: Discussionmentioning
confidence: 99%
“…Compliance and adherence to monitoring frequency and escalation recommendations are crucial to the functioning of NEWS. Previous studies have shown that adherence to recommended monitoring frequency may sometimes fall by the wayside during busy periods due to prioritization of other tasks, a lack of monitoring equipment and different understandings of how to apply escalation recommendations (Elliott et al, ; Smith & Aitken, ). Our findings indicate that the possible reasons for non‐compliance are more complex and are related to nurses’ beliefs regarding the role of their professional competence and judgement and their opinions on the reliability of NEWS.…”
Section: Discussionmentioning
confidence: 99%
“…However, contextual factors of workload pressures and staffing resources mitigate against ward based education due to a resistance of releasing staff for training. This review and other studies highlight that ongoing multiprofessional courses with practical applicability and opportunities to implement learning in practice are required for successful learning transfer and to breakdown cultural and professional boundaries (Baker-McClearn & Carmel 2008, Campello et al 2009, Calzavacca et al 2010, Smith & Aitken 2015.…”
Section: Ept Twomentioning
confidence: 99%